APLIKASI DATA CITRA SATELIT LANDSAT UNTUK PEMANTAUAN DINAMIKA PESISIR MUARA DAS BARITO DAN SEKITARNYA - Abdur Rahman (Fish Scientiae, 2019)
Have happened damage of environmental habitat of mangrove and abrasi of akresi causing its excelsior of face irrigate alongside DAS River of Barito (DAS Martapura, DAS Alalak and of DAS Kuin), because the happening of process of abrasi and of akresi that happened alongside coastline, especially DAS Martapura, DAS Alalak and DAS Kuin. Classification exploiting of farm and its conversion and also change of coastal area in the form of and akresi of abrasi alongside research area coast in analysis by exploiting information of satellite image data of Landsat temporal multi which in obtaining on 29 June year 1985, and 03 September 2006. Domination exploiting of farm in the form of HPH, settlement and mining with farm conversion at forest for other exploiting give big enough erosion impact with regional and natural coastal area that make-up of akresi especially part of river estuary (delta). Seen Change Trend at coastal area in research area during 21 year was abrasi equal to 294,55 m2 in Estuary area S. Martapura, 75,53 m2 around estuary S. Alalak. And change of Abrasi equal to 177,42 m2 , and akresi equal to 610,86 m2 around Estuary S. Barito / kuin).